Encyclopaedia Britannica deluxe cd 2000. - Encyclopaedia Britannica, inc. (Oxford : Oxford University Press, 1994)
Electronic encyclopedia containing the entire text of 83000+ articles, 6500+ photos and illustrations, 1 hour video, 1500+ maps, direct access* to 125000+ internet sites through Britannica.co.uk, New Oxford Dictionary of English, Interactive Timeline, New Multimedia spotlichts, new research assistant, new context bar navigation, new quick search
Advanced search disc -- Multimedia disc.
Windows system requirements: Windows 95/98 or Windows NT 4.0; 133 MHz Pentium processor or higher recommended, 32MB RAM, 100MB free hard-disk space (plus 50 MB for IE 5.0), 2X or faster CD-ROM drive, SVGA monitor / display card 800x600, 16-bit colour, sound card and speakers, mouse, printer recommended.
Keywords: Electronic encyclopaedia; CD-ROMs.